Long-Term Durability of Basalt Fiber-Reinforced Polymer (BFRP) Sheets and the Epoxy Resin Matrix under a Wet–Dry Cyclic Condition in a Chloride-Containing Environment - Zhongyu Lu (Polymers, 2017)
Basalt fiber-reinforced polymer (BFRP) composites are receiving increasing attention as they represent a low-cost green source of raw materials. FRP composites have to face harsh environments, such as chloride ions in coastal marine environments or cold regions with salt deicing. The resistance of FRPs subjected to the above environments is critical for the safe design and application of BFRP composites. In the present paper, the long-term durability of BFRP sheets and the epoxy resin matrix in a wet–dry cyclic environment containing chloride ions was studied. The specimens of the BFRP sheet and epoxy resin matrix were exposed to alternative conditions of 8-h immersion in 3.5% NaCl solution at 40 °C and 16-h drying at 25 °C and 60% relative humidity (RH). The specimens were removed from the exposure chamber at the end of the 180th, 270th and 360th cycles of exposure and were analyzed for degradation with tensile tests, scanning electron microscopy (SEM) and void volume fractions. It was found that the tensile modulus of the BFRP sheet increased by 3.4%, and the tensile strength and ultimate strain decreased by 45% and 65%, respectively, after the 360th cycle of exposure. For the epoxy resin matrix, the tensile strength, tensile modulus and ultimate strain decreased by 27.8%, 3.2% and 64.8% after the 360th cycle of exposure, respectively. The results indicated that the degradation of the BFRP sheet was dominated by the damage of the interface between the basalt fiber and epoxy resin matrix. In addition, salt precipitate accelerated the fiber–matrix interfacial debonding, and hydrolysis of the epoxy resin matrix resulted in many voids, which accelerated the degradation of the BFRP sheet.